Akad Gadai (Rahn) pada Pembiayaan Syari’ah (Analisis SWOT pada KSPPS Karomah di Pacuh Balongpanggang Gresik) - Misbahul Khoir (Akademika, 2020)
Rahn's financing is the most dominant financing in the Barokah Amanah Family of KSPPS.  From this reason, the authors chose the KSPPS Karomah object in Pacuh village, Balongpangang sub-district, Gresik district to be investigated. The goal of this research is to be able to provide as much detailed and up-to-date information as possible regarding the mechanism of rahn financing using ATM collateral and Savings Books and its contribution both internally to the growth of cooperative, SHU and its benefits for members  and surrounding communities in general. Interestingly, even though KPSPS Karomah was only established in the last two months of 2018, it has member a lot of especially for its rahn financing and has used a very effective online application and facilitates financial management in KSPPS Karomah. This research is a field-based qualitative research by making field data such as interviews, observations and documentation as primary data. By carrying out the process of organizing data, data reduction, data display, analysis and then finding conclusions. From this research is able by found out the mechanism and procedure of disbursement of Rahn contract financing using ATM collateral and savings books at KSPPS Karomah and analyze using SWOT. The results turned out to be very effective and the number of members could quickly multiply and could quickly develop because there was synergy (cohesion of Debtor data) or cooperative members with existing PKH members and BPNT social programs.